2018
DOI: 10.2331/suisan.18-00010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of balenine in muscle extract of opah <i>Lampris guttatus</i> with automatic amino acid analyzer

Abstract: We examined the method of analysis and quantitation of balenine (Bal) previously reported. In this method, Bal in muscle extract was hydrolyzed to 3-methylhistidine (3-Mehis) and b-alanine in 6 M hydrochloric acid heated at 110°C for 24 hours, analyzed and quantitated 3-Mehis by automatic amino acid analyzer. And it was found that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Harris and Milne (1987) suggested that BAL was distributed, albeit at a low level, in the skeletal muscles of a number of common mammals, including humans, rats, and rabbits. Recently, Omura et al (2018) reported that the muscle in opah (Lampris guttatus) showed a remarkably high BAL level of 2561 ± 436 mg/100 g, which is much higher than that recorded in baleen whales (1889 mg/100 g). Meanwhile, a number of studies on BAL bioactivity and function have been carried out since 2000.…”
Section: Introductionmentioning
confidence: 81%
“…Harris and Milne (1987) suggested that BAL was distributed, albeit at a low level, in the skeletal muscles of a number of common mammals, including humans, rats, and rabbits. Recently, Omura et al (2018) reported that the muscle in opah (Lampris guttatus) showed a remarkably high BAL level of 2561 ± 436 mg/100 g, which is much higher than that recorded in baleen whales (1889 mg/100 g). Meanwhile, a number of studies on BAL bioactivity and function have been carried out since 2000.…”
Section: Introductionmentioning
confidence: 81%
“…The biological origin of N τ-methylhistidine has been documented in more detail. N τ-methylation is a common modification of proteins such as the skeletal muscle proteins actin and myosin or the β-alanyl- N τ - methylhistidine dipeptide balenine. Consistent with an animal origin, the concentration of N τ-methylhistidine in human urine strictly correlated with dietary meat intake. Accordingly, several Clostridia species that are common members of the gastrointestinal microbiome contain N τ-methylhistidine degrading enzymes (Table S5). However, most species with this activity are saprophytic soil-dwelling bacteria.…”
Section: Biogenic Origin Of N-methylformamide and Nτ-methylhistidinementioning
confidence: 97%
“…However, because of its distribution in inedible animal muscles, the health functionalities of Bal as a food material have not been fully studied in human trials. Very recently, Bal was detected in the muscles of opah (Lampris guttatus), a mesopelagic and regionally endothermic fish, in high concentrations [ 22 ]. Omura et al detected 18.89 and 25.61 g/kg wet weight of Bal in minke whale and opah, respectively, but none in bigeye tuna and albacore.…”
Section: Introductionmentioning
confidence: 99%